2010
DOI: 10.4049/jimmunol.1000872
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Roles of Hepatocyte- and Myeloid Cell-Derived IL-1 Receptor Antagonist during Endotoxemia and Sterile Inflammation in Mice

Abstract: Material Supplementary 2.DC1http://www.jimmunol.org/content/suppl/2010/07/16/jimmunol.100087

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 40 publications
1
23
0
Order By: Relevance
“…Thus, transferred B cells may indeed modulate the functions of innate immune cells in lung and spleen to also promote regulatory dendritic cells or macrophages capable of producing IL-10 and other innate immune regulators (reviewed in references 85 and 86). This finding would be consistent with the concomitant upregulation of IL-10, IL-27, and also IL1Ra observed in B cell-transferred IFrag Ϫ/Ϫ mice (80,87,88). In support of this, we found in preliminary experiments that coculture of B cells with pulmonary CD11b…”
Section: Discussionsupporting
confidence: 88%
“…Thus, transferred B cells may indeed modulate the functions of innate immune cells in lung and spleen to also promote regulatory dendritic cells or macrophages capable of producing IL-10 and other innate immune regulators (reviewed in references 85 and 86). This finding would be consistent with the concomitant upregulation of IL-10, IL-27, and also IL1Ra observed in B cell-transferred IFrag Ϫ/Ϫ mice (80,87,88). In support of this, we found in preliminary experiments that coculture of B cells with pulmonary CD11b…”
Section: Discussionsupporting
confidence: 88%
“…qualitative difference between IL-1Ra and IL-1R2. The finding that IL-1R2 plays a marginal role, if any, in the control of systemic responses to acute administration of IL-1 or LPS, whereas IL-1Ra plays a crucial role in these two inflammatory situations (28,29), emphasizes the difference between these two IL-1 inhibitors. Even though neutrophils are recruited from the bone marrow to the circulation in systemic responses, a concentration of neutrophils and IL-1R2 as high as that locally reached in arthritic joints is not achieved, suggesting a predominantly local regulatory function of IL-1R2.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that IL-1Ra, another regulator of IL-1 bioactivity, plays a critical role during IL-1b-induced sterile inflammation (28) and lethal endotoxemia (28,29). The assessment of serum levels of IL-6, CXCL1, and CXCL2 as markers for inflammation at different time points upon administration of two doses of IL-1b at 0 and 12 h showed no difference between IL-1R2 2/2 and WT mice, except for significantly higher IL-6 levels in serum of IL-1R2 2/2 compared with WT mice 36 h after the first IL-1b injection (Fig.…”
Section: No Effect Of Il-1r2 Deficiency On Il-1b-induced Sterile Inflmentioning
confidence: 99%
“…However, treatment with recombinant IL1RN (anakinra) has been shown to be antidiabetic, improving both insulin sensitivity and beta cell function (38,39), suggesting that the increase in IL1RN may represent a compensatory change to proinflammatory signals. The liver is a major source of circulating ILRN (40). PGC-1␣ is induced in liver by caloric restriction and exercise (both conditions improving insulin sensitivity and glucose tolerance (41)).…”
Section: Discussionmentioning
confidence: 99%